IMPLEMENTASI STRATEGI CORPORATE SOCIAL RESPONSIBILITY - Sjamsu Alam Lawelle (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
Strategy Corporate Social Responsibility as an attempt to achieve good corporate governance,good corporate citizenship and good business ethics of a business entity, so the company is notenough to just think about the interests of owners of capital, but also to meet the interests of allstakeholders. The purpose of this study was to analyze the influence of CSR strategy for CSRimplementation. This study used quantitative methods, and design studies testing the hypothesisor hypotheses. The samples by purposive sampling method. The sample consisted of a director,senior manager, senior assistant managers, supervisors and staff / specialists. In the analysisconducted two initial test, the test validity and reliability testing. Then test compliance withAnova, Correlation and simple linear regression. Results of hypothesis testing showed CSRstrategy has a strong and direct relationship with the implementation of CSR with correlationnumber 0,437, and the value of R Square 0,191 means that 19% of the company's CSR strategyvariables can be explained by the effect of implementation of CSR or CSR implementation ofthe company's CSR strategy by 19% while the remaining 81% is explained by other factorsoutside variables CSR implementation. CSR strategies are packed with good company andintegrated with its business strategy will be a positive influence and gain support from thecommunity and other stakeholders.Keyword : Corporate Social Responsibility, Strategy, Implementation